Respuesta :
6(7+5) + 3 =
42 + 30 + 3 = <<<< This one is the equivalent expression
If you wanted to continue and solve...
72 + 3 =
75
42 + 30 + 3 = <<<< This one is the equivalent expression
If you wanted to continue and solve...
72 + 3 =
75
Mathematical expressions are expressions that uses at least one mathematical operator
- The expression is [tex]\mathbf{(7+5) \times 6+3}[/tex]
- The equivalent expression is: 42 + 30 + 3
(a) The expression
Only one expression fits the given description.
And the expression is (7+5)x6+3
(b) Equivalent expression of (a)
In (a), we have:
[tex]\mathbf{(7+5) \times 6+3}[/tex]
Distribute the expression as follows:
[tex]\mathbf{(7+5) \times 6+3 = 7 \times 6 + 5 \times 6 + 3}[/tex]
Evaluate the products
[tex]\mathbf{(7+5) \times 6+3 = 42 + 30 + 3}[/tex]
Hence, the equivalent expression is 42 + 30 + 3
Read more about mathematical expressions at:
https://brainly.com/question/20596193